Preface - Burczyński, Tadeusz (Computer Assisted Methods in Engineering and Science, 2019)
We present the next issue of CAMES, in which four articles addressing inverse problems are to be found. These articles were presented during the 5th International Conference on Inverse Problems Methods IPM 2019 which was held at the Kombornia Manor Hotel, May 2019, where in the historical environment of a manor complex, surrounded by the English landscape park, one could both relax and find an inspiration for further research.